Relevância dos aspectos nutricionais na sobrevida de pacientes com Doença do Neurônio Motor - Stanich, Patricia [UNIFESP] (2011)
Aims. To evaluate the effect of nutrition on survival of patients with Motor Neurone Disease (MND) and present the predictor variables for indications of nutritional therapy, percutaneous endoscopic gastrostomy (PEG). Methods. It was a retrospective longitudinal cohort study, from 2000 to 2008, and the sample consisted of 128 patients with MND. The variables investigated were clinical, nutritional and respiratory were analysed. Analyses were conducted by adopting the survival as the dependent variable. The survival curve was evaluated by Kaplain - Meier. The variables that had a significance level of 20% (p <0.20) were selected for the proportional regression model of Cox. Results. One hundred and eleven patients underwent gastrostomy, and 59 limb onset (ALS) and 52 with bulbar onset (PBP). Malnutrition was present in 32% of the population before PEG, most frequently in patients with limb onset. The survival time after PEG was 10.5 months for patients with PBP and 16 months for ALS (p <0.05). Variables associated with survival were: early indication in the PEG, for ALS and PBP; reduction of FVC% and BMI before PEG (hazard ratio of 0, 254, p = 0, 007) for patients with limb onset and exclusion of oral feeding and tracheostomy (hazard ratio of 0, 345, p = 0, 014) for patients with bulbar onset. Conclusions. Early insertion of percutaneous endoscopic gastrostomy, from the time diagnosis was a protective factor for patient survival. Malnutrition was a bad prognostic factor, especially for patients with limb onset. Nutritional surveillance for disease progression may improve results when the goal is to increase the survival of patients with MND / ALS.